Metabolic profiling for identification of potential biomarkers in potato tuber extracts associated with tolerance to Spongospora subterranea f. sp. subterranea infection - Apostolides, Zeno (University of Pretoria, 2020)
Dissertation (MSc)--University of Pretoria, 2019.